Analysis of Point of View in Adele Park’s Novel Lies Lies Lies - Pakaya, Yesi Yustika; Baga, Magdalena; Muhamad, Farid (Transbahasa, 2023)
The aim of this research is to find and analyze the point of view utilized in the novel Adele Park Lies Lies Lies. This research utilized structural analysis, which allows the researcher to focus on the underlying patterns present in the text, particularly concerning the point of view. The data were obtained from the novel entitled Lies Lies Lies by Adele Parks and this research focused on exploring how the first-person point of view Daisy character and the third-person point of view Simon character in each other interact and contribute to the overall meaning of the story. In this research, data collection than carried out using several specific techniques including an in-depth reading of the entire novel, collecting data concerning two primary types of point of view found in the novel: first-person singular and third-person singular, identifying the specific points of view, and proceeding to analyze each of the sentences that utilized first-person singular and third-person singular point of view. The technique of analyzing data using a structural approach essential in the context of this research, as it provides a systematic and rigorous method to unravel the intricacies of the novel Lies Lies Lies by Adele Parks. The results showed that in Lies Lies Lies, the use of first-person and third-person point of views allows the reader to experience the story from different point of view. The first-person point of view highlights situations experienced by Daisy throughout the novel, which is her twisted marriage story with her husband, Simon. On the other hand, the third-person point of view highlights the situation experienced by Simon, which is his experience in dealing with his marriage, his life in prison, and the fact that his daughter was not his